Effectiveness of Acellular Pertussis Vaccine in Older Adults: Nested Matched Case-control Study. (26th August 2019) - Liu, Bette C; He, Wen-Qiang; Newall, Anthony T; Quinn, Helen E; Bartlett, Mark; Hayen, Andrew; Sheppeard, Vicky; Rose, Nectarios; Macintyre, C Raina; Mcintyre, Peter
Abstract: Background: Despite recommendations that older adults receive acellular pertussis vaccines, data on direct effectiveness in adults aged over 50 years are sparse. Methods: A case-control study nested within an adult cohort. Cases were identified from linked pertussis notifications and each matched to 3 controls on age, sex, and cohort recruitment date. Cases and controls were invited to complete a questionnaire, with verification of vaccination status by their primary care provider. Vaccine effectiveness (VE) was estimated by conditional logistic regression, with adjustment for reported contact with children and area of residence. Results: Of 1112 notified cases in the cohort, we had complete data for 333 cases and 506 controls. Among 172 PCR-diagnosed cases (mean age, 61 years), 11.2% versus 19.5% of controls had provider-verified pertussis vaccination, on average, 3.2 years earlier. Adjusted VE against PCR-diagnosed pertussis was 52% (95% CI, 15–73%), nonsignificantly higher if vaccinated within 2 years (63%; −5–87%). Adjusted VE was similar in adults born before 1950, presumed primed by natural infection (51%; −8–77%) versus those born 1950 or later who may have received whole-cell pertussis vaccine (53%; −11–80%) ( P -heterogeneity = 0.9). Among 156 cases identified by single-point serology, adjusted VE was −55% (−177–13%). Conclusions: We found modest protection against PCR-confirmed pertussis among older adults (mean age, 61 years; range, 46–81 years) within 5 years after acellular vaccine. The most likely explanation for the markedly divergent VE estimate from cases identified by single-titer serology is misclassification arising from limited diagnostic specificity in our setting. Abstract : Only 1 earlier study has quantified the direct protection afforded by acellular pertussis vaccine in older adults. Among adults (mean age, 61 years; range, 46–81 years), we estimated acellular pertussis vaccine was 50% effective in preventing polymerase chain reaction (PCR)-confirmed pertussis infection.